(untitled) (GYMNASIUM, 2017)
Physical education and sport are activities of national interest, with an increasing role in harmonious physical development, health enhancing, developing motor qualities, intellectual and moral. Sports activities, carried out by a younger generation, they echo the motor and behavioral plan. This paper submit the relationship between sports activities carried out by teenagers’ girl, they induced effects and values ​​promoted by sport activities. The study was conducted in 2011-2012 at two high schools in Bucharest. During this experimental research, we designed and implemented: motric programs and cognitive programs – capable to enrich the teenagers knowledge according to their interests. Bibliography which helped this research is constituting in psychology studies, pedagogy studies, sociology studies. Physical education and sport contribute to the educational ideal and the social formation of personality to embodies responsible and active participant in solving the problems of society.